Foundations of Incomplete Contracts - Hart, Oliver; Moore, John (Review of Economic Studies, 1999)
In the last few years, a new area has emerged in economic theory, which goes under the heading of 'incomplete contracting'. However, almost since its inception, the theory has been under attack for its lack of rigorous foundations. In this paper we evaluate some of the criticisms that have been made of the theory, in particular, those in Maskin and Tirole (1998a). In doing so, we develop a model that provides a rigorous foundation for the idea that contracts are incomplete.